Responses to the critics - von Schomberg, René (NOvation — Critical Studies of Innovation, 2024)
Personal comment on the responses to “Towards a New Ethos of Science or a Reform of the Institution of Science? Merton Revisited and the Prospects of Institutionalizing the Research Values of Openness and Mutual Responsiveness” by René von Schomberg.